Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada Donkent Cafe Bengkulu - Rossa Ayuni; Serli Permatasari (Universitas Dehasen Bengkulu, 2022)
This study aims to determine the Marketing Strategy in Increasing Sales Volume at Donkent Cafe Bengkulu. The method used in this research is descriptive. In this study the data and data sources used are primary data and secondary data. Collecting data using observation, interviews, documentation. Data analysis consists of data collection, data reduction, data presentation, drawing conclusions,. Based on the results of research at Donkent Cafe Bengkulu, the following results were obtained: (1) from the product strategy using quality raw materials; (2) from the price strategy (price) prices that can be reached by all levels of society with a variety of payment systems; (3) from the strategy the place has a strategic location which is located on the main road of the highway; (4) from promotion strategies using social media such as Instagram, Facebook, WhatsApp, TikTok and other social media.